The Relationship Between Leadership Style of The Head of Agency and The Employees’ Performance in The Environmental Agency of Biak Numfor Regency - S, Fatmawada (Jurnal Office, 2019)
This study aims to determine and explain the relationship between the leadership style of the head of the environmental agency with the employees’ performance. This study uses a quantitative survey approach that is ex-post facto and principal on phenomena or events that have occurred and are still ongoing until the study is conducted, using descriptive statistical data analysis techniques, inferential descriptive analysis, and testing requirements analysis including normative data tests conducted by using the SPSS program with the Kolmogorov Smirnov One Sample test. The results of this study stated that the relationship between leadership style or leadership behavior of the head of service to the performance of employees in the Environmental Service Agency of Biak Numfor regency is not so large, only about 10 percent, which meant that the employee's performance was more determined by other variables not included in this study.